2005
DOI: 10.1245/aso.2005.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of Primary Tumors in Patients Who Present With Stage IV Colorectal Cancer: An Analysis of Surveillance, Epidemiology, and End Results Data, 1988 to 2000

Abstract: Most patients who present with stage IV colorectal cancer undergo resection of the primary tumor. The proportion of patients undergoing resection depends on patient age and race and the anatomical location of the primary tumor. The degree to which case selection explains the treatment and survival differences observed is not known. Further investigation of the role of surgery in the management of incurable stage IV colorectal cancer is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
186
2
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(214 citation statements)
references
References 40 publications
8
186
2
15
Order By: Relevance
“…For stage IV disease, the likelihood of colorectal resection declined with increasing age. This was also observed in two US series (Temple et al, 2004;Cook et al, 2005), although in both series the effect was mainly limited to the very old (80 or 85 and over), whereas in our study there was a steady decrease with increasing age (60% of the under 65s had a resection, whereas only 51% aged 65 -74 and 42% aged X75 did). In addition to having more co-morbid conditions (Yancik et al, 1998), older patients are more likely to require emergency surgery (Colorectal Cancer Collaborative Group, 2000a), and these factors may influence the proportion resected in different populations.…”
Section: Factors Associated With Treatmentsupporting
confidence: 81%
See 2 more Smart Citations
“…For stage IV disease, the likelihood of colorectal resection declined with increasing age. This was also observed in two US series (Temple et al, 2004;Cook et al, 2005), although in both series the effect was mainly limited to the very old (80 or 85 and over), whereas in our study there was a steady decrease with increasing age (60% of the under 65s had a resection, whereas only 51% aged 65 -74 and 42% aged X75 did). In addition to having more co-morbid conditions (Yancik et al, 1998), older patients are more likely to require emergency surgery (Colorectal Cancer Collaborative Group, 2000a), and these factors may influence the proportion resected in different populations.…”
Section: Factors Associated With Treatmentsupporting
confidence: 81%
“…The colorectal resection rate was constant over time, in contrast to a US study that reported a slight, but significant, decrease during 1988 -2000 (Cook et al, 2005). Our frequency of 78% undergoing resection was lower than that in US studies (90 -92%; Ciccolallo et al, 2005) but close to figures for European community practice (Gatta et al, 2000;Pitchforth et al, 2002).…”
Section: Treatment Rates and Trends Over Timecontrasting
confidence: 81%
See 1 more Smart Citation
“…About 20-25% of patients with newly diagnosed CRC present with distant metastases (2)(3)(4), and only a small population of these patients can undergo curative operation (5). For patients with unresectable metastatic tumors, the standard treatment is systemic chemotherapy.…”
Section: The Measurement Of Tils In the Primary Tumor Using The Methomentioning
confidence: 99%
“…A similar retrospective study by Cook et al reviewed 26,754 patients with CRC over a 12-year period. Of those patients, 17,658 were resected and demonstrated increased survival [23]. Survival in the group with colon cancer was 11 months following resection compared to 2 months when the primary was not removed (p ≤ 0.001).…”
Section: Management Of Colorectal Primary For Stage IV Diseasementioning
confidence: 99%